2021
DOI: 10.1186/s13046-021-01846-5
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop between TAZ and miR-942-3p modulates proliferation, angiogenesis, epithelial-mesenchymal transition process, glycometabolism and ROS homeostasis in human bladder cancer

Abstract: Background Transcriptional coactivator with PDZ-binding motif (TAZ) has been reported to be involved in tumor progression, angiogenesis, epithelial-mesenchymal transition (EMT), glycometabolic modulation and reactive oxygen species (ROS) buildup. Herein, the underlying molecular mechanisms of the TAZ-induced biological effects in bladder cancer were discovered. Methods qRT-PCR, western blotting and immunohistochemistry were performed to determine t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…MiR-942-3p promotes breast cancer progression by downregulating the expression of forkhead box protein A2 ( Zhang J. et al, 2019 ). A new positive-feedback loop was identified between miR-942-3p and a transcriptional coactivator with a PDZ-binding motif, which regulated the biological function of bladder cancer cells and illustrated that these targets might have therapeutic potential as targets for prostate cancer treatment ( Wang et al, 2021 ). The results of that study also suggest that miR-942-3p regulates the development of a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-942-3p promotes breast cancer progression by downregulating the expression of forkhead box protein A2 ( Zhang J. et al, 2019 ). A new positive-feedback loop was identified between miR-942-3p and a transcriptional coactivator with a PDZ-binding motif, which regulated the biological function of bladder cancer cells and illustrated that these targets might have therapeutic potential as targets for prostate cancer treatment ( Wang et al, 2021 ). The results of that study also suggest that miR-942-3p regulates the development of a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro experiments, such as CCK-8 assay, H&E staining, and IHC, have been previously described by us (Wang et al, 2020a(Wang et al, , 2021.…”
Section: Other In Vitro Experimentsmentioning
confidence: 99%
“…Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) are the downstream effectors of the Hippo pathway [ 27 ]. Studies have demonstrated the regulatory roles of YAP and TAZ in the EMT process [ 28 , 29 ]. The results showed that the levels of p-YAP and p-TAZ were markedly increased by ISLR silence while decreased by ISLR overexpression (Fig.…”
Section: Resultsmentioning
confidence: 99%